International court of justice judgment on the Nigeria-Cameroon borderland conflict: implications on Bakassi people (2018)
From time immemorial, States have been involved in various forms of border conflicts and the origin of these disputes is often times difficult to trace. For some of these conflicts, it can be said to have erupted due to the colonial ties shared by the States, for political motives or as a result of the natural resources found in such a border that will therein improve their economy. This paper analyses the border conflict that occurred between Nigeria and Cameroon which finally led the case to be taken to the International Court of Justice (ICJ) to settle the conflict. The conflict is peculiar in nature because it is not a conflict over waterways or airspace but a conflict over a territorial space that involved a group of people. The settlement pattern in one way or the other has impacted on the people occupying the disputed area. Such implication goes further to infer that when a border dispute that involves a group of people is settled, there is an after effect of such settlement whether positive or negative in nature. The outcome of the verdict was to avert a war but the situation of the Bakassi people after the ceding over the Bakassi Peninsula has not been palatable. Using primary, secondary sources of data collection and social constructivism as its theoretical framework, the paper argues that both States accepted and complied with the verdict of the International Court of Justice as a result of protecting their identities thus shaping their interest. The paper also posits that though the verdict did not rule in favour of the Bakassi people and the Nigerian government as majority would have wanted due to its peculiar nature, but it prevented a major outbreak of war.